Enterprise Risk Management Implementation and Earnings Quality: An Empirical Investigation on Nigerian Financial Sector - Omololu Adex Bamigboye; Isaiah Omotayo Fakunle; Olayinka Adedayo Erin (Magister Akuntansi FB-UK.Maranatha, 2024)
Researches on Enterprise Risk Management (ERM) have gained relevance in accounting and finance literature in recent years, due to more stringent regulations following the global financial crisis. Based on this recent development, this study investigates whether compliance with Enterprise Risk Management implementation impact earnings quality of fifty (50) financial firms in Nigeria. Generalised Method of Moments (GMM) estimator and difference-in-differences analysis were used to test the hypothesis of the study. We also use content analysis method to evaluate the ERM disclosure of the selected financial firms. The results shows that compliance with ERM strategy improves earnings quality and performance. In addition, the result reveals that the implementation of ERM contributes 45.6% increase to earnings quality during the post-ERM period (2019-2023) using the difference-in-differences method. This study contributes to knowledge in accounting and finance literature with respect to ERM research in under-investigated context (Sub-Saharan Africa) with a specific focus on Nigeria.